Seeds of discord: the ominous future of European agricultural sector under F2F EU directive and the nature restoration law - Catarinella, Piermauro; Kram, Suhardi; Min, Alfonso (Universiti Teknologi MARA, Perak, 2025)
In January 2024, a substantial gathering of tractors from diverse European regions converged upon Brussels, staging fervent demonstrations outside the premises of the European Commission and the European Parliament. These protests, persisting to date, are spearheaded by agricultural workers predominantly from medium and small enterprises, urging the European institutions to reconsider the regulations outlined in the Farm to Fork (F2F) directive and the Nature Restoration Law. These regulations are integral components of the European Green Deal, designed to aid the European Union in accomplishing its main objectives: maintaining Earth’s temperature within a 1.5°C threshold, achieving net-zero greenhouse gas emissions by 2050, curtailing pesticide usage by 50% by 2030, restoring ecosystems, promoting sustainable food production, and fostering innovation in the industry. Despite these ambitious goals, farmers contend that these rules are unsustainable, as they fail to consider the unique characteristics of various territories and production entities, thereby imposing bureaucratic constraints. Some stakeholders suggest that the regulations might not genuinely prioritize environmental protection; rather, they could be perceived as potentially favoring large multinational corporations. Notably, individual European governments disclaim any responsibility in this domain, as the entire purview falls under the jurisdiction of the Commission and the European Parliament. This research employs a qualitative approach, involving a comprehensive policy analysis of the F2F EU Directive and the Nature Restoration Law, a critical evaluation of political discourse from EU official documents, media scrutiny of contemporary European newspaper articles, and video interviews with protesting farmers. Through this multi-faceted analysis, the study endeavors to ascertain whether these regulations genuinely align with the EU’s environmental protection objectives or if they are rooted in ideological political choices that could jeopardize the livelihoods of European farmers. The findings underscore that the decisions of European institutions not only threaten the existence of medium and small-scale farmers but also compromise the production of natural and authentic goods traditionally linked to these agricultural practices. Consequently, the European agricultural sector faces the looming threat of extinction within a few years, potentially replaced by industries specializing in synthetic foods manufactured in laboratories.